The Last Word - Darryl Phillips (Communicare)
WHILST there seems to be a strong commit- ment by the government to reform the socio-political system, the basic task to market this reform policy to a most diverse electorate still remains at hand. Although "reform" may be a somewhat more esoteric and crucial product than soap powder or fast foods, it is no less real. And the marketing principles which apply are no different...